A rare case of condyloma acuminatum caused by HPV73 and HPV33 infection - Beilei He; Wei Wang; Weijian Dai; Kamran Ali; Qingyun Yang; Tingkai Xiang; Enyi Ye; Yangfan Wu; Zhangyu Bu (Elsevier, 2022)
Condyloma acuminatum (CA) is a sexually transmitted disease caused by human papillomavirus (HPV) infection, mainly by HPV DNA types 6 and 11. Except for HPV16 and HPV18, CA caused by other intermediate or high-risk subtypes is rare in clinical settings. Here, we report a case that was positive for HPV73 and 33 and negative for other common subtypes. This case highlights that caution should be taken in cases that are negative for common HPV subtypes but have typical clinical manifestations. That the detection of other subtypes and tissue biopsy should not be ignored.